Implementation of the HACCP Food Safety Management System in Ensuring the Quality of Taiyaki Products: A Field Study in the Japanese Food Industry - Fajar Apriansyah Ramlan; Kiki Sanjaya; Alchamdani Alchamdani; Stefiani Bengan Laba (Jurnal Locus Penelitian dan Pengabdian, 2026)
Bakery products with cream fillings, such as Mini Taiyaki, are highly susceptible to microbiological hazards, particularly at the post-heating stage, and therefore require stringent process controls to ensure product safety and quality. This study aims to analyze the implementation of the Hazard Analysis and Critical Control Point (HACCP) system along the Mini Taiyaki production line based on field data collected during an internship programme. The scope includes hazard analysis, identification of critical control points, determination of critical limits, monitoring and corrective action mechanisms, as well as the planning of microbiological verification and documentation. The study adopts a descriptive case study design focusing on a single production line, with data collected through structured observations across all process stages, review of standard operating procedures and production records, directed interviews with operators and quality assurance personnel, and the development of a microbiological verification plan covering finished products, cream fillings, the packaging environment, operators’ hands, air, and process water. Hazard analysis was conducted using a probability–severity matrix to determine hazard significance, while the identification of critical control points employed a decision tree adapted to the characteristics of the process. The results indicate that the dominant hazards are biological in nature, with five main critical control points identified: baking, rapid cooling, metal detection, packaging hygiene, and finished product storage. The system design emphasizes microbial elimination, prevention of microbial growth, and avoidance of recontamination. Consistent implementation with disciplined monitoring, corrective actions, microbiological verification, and FSMS integration strengthens sustainable safety and quality assurance for Mini Taiyaki